Decoding techniques for indoors navigation using VLC - Louro, Paula (2022)
In recent years, devices with wireless communication capabilities have generated a growing interest in indoor navigation. Indoor localization and proximity detection is becoming increasingly attractive due to the emergence of the Internet of Things (IoT) and the inherent end-to-end connectivity of billions of devices. In a closed space, GPS has poor, unreliable performance, requiring alternative techniques and wireless technologies. In this paper, we propose the use of Visible Light Communication (VLC) to support guidance and communication for signaling in an indoor environment. Research focuses mainly on the development of navigation VLC systems, transmission of control data information, and decoding techniques. The communication system uses RGB white LEDs as emitters and pinpin photodiodes with selective spectral sensitivity as receivers. Downlink communication is established between the infra-structure and the mobile user. The decoding strategy is based on accurate calibration of the output signal and uses bit error control methods to reduce the BER of the system. In this paper, we will describe the coding schemes and decoding algorithms, as well as the characteristics of transmitters and receivers.